SENSORY ATTRIBUTES AND BIOCHEMICAL CHARACTERISTICS OF UNDERUTILIZED FRUIT, PRUNUS NAPAULENSIS (SER.) STEUD - PHAREICHON KASHUNG (The Journal of Research ANGRAU, 2025)
This study conducted in 2023, provides a comprehensive analysis of Prunus napaulensis (Ser.) Steud, focusing on its physical, biochemical, and sensory attributes. It aims to explore the biochemical composition and sensory profile to provide insights to its nutritional and bioactive compounds and its consumer preferences. Phytochemical screening in aqueous, ethanol and methanol extracts revealed the presence of various bioactive compounds such as flavonoids, tannins, phenols, anthocyanin and alkaloids. Antioxidant activity (DPPH assay) indicated varying degrees of radical scavenging activity in aqueous, ethanol and methanol solvents with IC50 values recorded at 46.90µg/mL, 144.62µl/mL and 51.68µL/mL respectively. The fruit exhibited characteristic physical dimensions and biochemical composition with good amounts of iron (3.03 ± 0.15 mg), calcium (80 ± 2 mg), potassium (371.33 ± 2.52 mg), magnesium (29.33 ± 2.52 mg), zinc (2.6 ± 0.45 mg), vitamin C (49.36 ± 3.92 mg) and significant levels of anthocyanin (244 ± 58.59 mg) highlighting its nutritional value. The Descriptive sensory analysis of the fruit provided an insight into the appearance, colour, aroma, flavour, firmness, taste and juiciness of the fruit contributing to a comprehensive understanding of its sensory attributes and consumer preferences. Thus, the study underscores the significance of the fruit and its potential commercial value and further research and exploration in both the food industry and healthcare sectors.